A polypropylene composite current collector base film and a method for preparing the same

CN122917438APending Publication Date: 2026-10-16扬州博恒新能源材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611003566.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

第二,力学性能不足

Benefits of technology

1、本发明通过改性纳米蒙脱土与多功能POSS改性环三磷腈阻燃增强剂的复配,并配合马来酸酐接枝聚丙烯相容剂及优化的助剂体系,在聚丙烯基体中构建了均匀分散、界面结合牢固的多相复合结构。本发明制备得到的基膜同时具备优异的力学性能、阻燃性能、耐热尺寸稳定性和耐电解液性能,能够满足高安全性、高能量密度锂离子电池集流体的严苛使用要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1783407980496-000001
    Figure REF-OBJ-1783407980496-000001
Patent Text Reader

Abstract

The present application relates to the field of current collector base film, and particularly relates to a polypropylene composite current collector base film and a preparation method thereof.The polypropylene composite current collector base film comprises, in terms of weight parts, 100 parts of polypropylene resin, 3-8 parts of modified nano montmorillonite, 10-15 parts of flame-retardant reinforcing agent, 6-10 parts of compatilizer, 0.4-1.0 parts of antioxidant, 0.2-0.5 parts of ultraviolet absorber and 0.3-0.7 parts of lubricant.The present application constructs a multiphase composite structure which is uniformly dispersed and firmly combined in the interface of the polypropylene matrix, solves the problem of mutual contradiction between the flame retardation and mechanical properties of the traditional flame retardant, and makes the prepared base film simultaneously have excellent mechanical properties, flame retardation, heat resistance and dimension stability and electrolyte resistance, so as to meet the strict use requirements of high safety and high energy density lithium ion battery current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of current collector base films, and more specifically to a polypropylene composite current collector base film and its preparation method. Background Technology

[0002] Current collectors are an indispensable core component in lithium-ion batteries. Their main function is to carry the active material of the electrodes, collect and output the current generated by the active material, and simultaneously input external current to the active material. Traditional lithium-ion battery current collectors mainly use pure metal copper foil or aluminum foil. Although they have excellent conductivity and mechanical properties, they have inherent drawbacks such as heavy weight, high cost, and poor safety. When subjected to mechanical damage such as squeezing, puncture, and impact, or electrical stress damage such as overcharging and short circuits, the metal foil is prone to developing sharp burrs, causing internal short circuits, which can lead to thermal runaway or even explosion of the battery. To address these issues, composite current collectors have emerged. Composite current collectors employ a sandwich structure design of a metal layer-polymer base film-metal layer. By replacing most of the metal materials with the polymer base film, the weight of the current collector can be reduced by 50%-80%, significantly increasing the battery's weight energy density by 5%-10%. Simultaneously, the polymer base film undergoes a melting effect when heated, forming a point circuit, which effectively prevents heat propagation and greatly improves battery safety.

[0003] Currently, commonly used polymer base film materials for composite current collectors include polyethylene terephthalate (PET), polypropylene (PP), and polyimide (PI). Among them, polypropylene (PP) is considered to be a composite current collector base film material with great industrialization potential due to its advantages such as low cost, wide availability, low density, excellent chemical stability, resistance to electrolyte corrosion, good flexibility, and high elongation at break. However, ordinary polypropylene base films still face the following serious challenges when applied to composite current collectors: First, extremely low surface polarity and weak interfacial bonding with metal layers. The polypropylene molecular chain has a non-polar hydrocarbon structure with low surface energy, which differs significantly from the surface energy of metal layers such as copper and aluminum, resulting in weak van der Waals forces as the main interfacial forces. Second, insufficient mechanical properties. Ordinary polypropylene base films are prone to tensile deformation and tearing during processing, leading to low yield rates. Third, poor heat resistance and dimensional stability. When preparing metal layers using vacuum deposition or magnetron sputtering, the process temperature is relatively high. Ordinary polypropylene films are prone to thermal shrinkage, warping, and even melting, which disrupts the continuity and density of the metal layer and affects its conductivity. Fourth, it has poor flame retardancy and aging resistance. Polypropylene is highly flammable, which can exacerbate the fire risk in the event of battery thermal runaway. Furthermore, polypropylene is susceptible to thermal-oxidative aging during use, leading to a decline in its mechanical properties and a shortened service life.

[0004] Existing technologies mostly modify polypropylene composite current collector membranes by adding single inorganic fillers or flame retardants, but these methods suffer from drawbacks such as poor filler dispersibility, weak interfacial bonding, and limited performance improvement. Furthermore, existing modification techniques often only address a single problem, failing to simultaneously meet multiple requirements such as mechanical properties, flame retardancy, heat resistance, dimensional stability, and electrolyte resistance. Therefore, developing a polypropylene composite current collector membrane with superior comprehensive performance is of great significance. Summary of the Invention

[0005] To address the problems existing in the prior art, the purpose of this invention is to provide a polypropylene composite current collector base film and its preparation method.

[0006] The objective of this invention is achieved through the following technical solution: In a first aspect, the present invention provides a polypropylene composite current collector base film, comprising, by weight parts: 100 parts polypropylene resin, 3-8 parts modified nano-montmorillonite, 10-15 parts flame retardant reinforcing agent, 6-10 parts compatibilizer, 0.4-1.0 parts antioxidant, 0.2-0.5 parts ultraviolet absorber and 0.3-0.7 parts lubricant.

[0007] Preferably, the polypropylene resin is homopolymer polypropylene with a melt flow index of 2.0-4.0 g / 10 min (230℃, 2.16 kg).

[0008] Preferably, the modified nano-montmorillonite is obtained by first modifying sodium-based montmorillonite in situ with dopamine, and then subjecting it to heat treatment.

[0009] More preferably, the method for preparing the modified nano-montmorillonite includes: 10g of sodium montmorillonite was dispersed in Tris-HCl buffer to prepare a 5% (w / w) suspension, and ultrasonically dispersed. 2-3g of dopamine hydrochloride was added, and the mixture was stirred and reacted at room temperature in the dark for 12-36 hours. After the reaction was completed, the mixture was centrifuged, washed, vacuum dried, and heat-treated in a tube furnace at 150℃. After natural cooling, the mixture was sieved to obtain modified nano-montmorillonite.

[0010] Preferably, the compatibilizer is maleic anhydride-grafted polypropylene (PP-g-MAH) with a grafting rate of 1.0-2.0 wt% and a melt flow index of 6-12 g / 10 min (230℃, 2.16 kg).

[0011] Preferably, the antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1-3.

[0012] Preferably, the ultraviolet absorber is at least one of UV-327, UV-770, and UV-312.

[0013] Preferably, the lubricant is a compound of zinc stearate and polyethylene wax in a mass ratio of 1-2:1-2.

[0014] Preferably, the method for preparing the flame retardant enhancer includes: S1. Prepare solutions of hexachlorocyclotriphosphazene and allylamine separately. Under nitrogen protection and ice bath conditions, slowly add the allylamine solution to the hexachlorocyclotriphosphazene solution. After the addition is complete, heat to 40-50℃ and react for 12-16 hours. After the reaction is complete, cool to room temperature, filter to remove the precipitate, rotate to dryness, and then wash and dry to obtain the hexaallyltriphosphazene intermediate. S2. Under nitrogen protection, mercaptopropyl-heptaisobutylsilsesquioxane (POSS-SH) and hexaallyltriphosphazene intermediate are dissolved in N,N-dimethylformamide, a photoinitiator is added, the reaction solution is irradiated with ultraviolet light, and the reaction is carried out at room temperature for 3-5 hours. After the reaction is completed, the flame retardant enhancer is obtained by precipitation, filtration, washing and drying.

[0015] Preferably, in S1, the mass ratio of hexachlorocyclotriphosphazene to allylamine is 3.48:5.71-7.13.

[0016] More preferably, in S1, the mass ratio of hexachlorocyclotriphosphazene to allylamine is 3.48:3.89.

[0017] Preferably, in S2, the molecular weight of mercaptopropyl-heptaisobutylsilsesquioxane (POSS-SH) is 893.6 g / mol.

[0018] Preferably, in S2, the mass ratio of mercaptopropyl-heptaisobutylsilsesquioxane (POSS-SH) to hexaallyltriphosphazene intermediate is 11.5-12.5:1.

[0019] Preferably, in S2, the mass ratio of mercaptopropyl-heptaisobutylsilsesquioxane (POSS-SH) to hexaallyltriphosphazene intermediate is 12:1.

[0020] Preferably, in step S2, the photoinitiator is dimethyl benzoate (DMPA), and the amount added is 0.5%-1.5% of the mass of mercaptopropyl-heptaisobutylsilsesquioxane.

[0021] Secondly, the present invention provides a method for preparing a polypropylene composite current collector-based film, comprising the following steps: Step 1: Dry all raw materials before use to remove moisture and prevent the formation of bubbles and degradation during processing; Step 2: Accurately weigh each dried raw material according to the weight proportions, add all raw materials into a high-speed mixer, and mix at a speed of 1000-1500 r / min for 5-8 minutes to ensure that the components are evenly dispersed and to obtain a premix. Step 3: Add the premixed material to a twin-screw extruder for melt blending. The temperatures of each section of the twin-screw extruder are set as follows: Zone 1 180-190℃, Zone 2 190-200℃, Zone 3 200-210℃, Zone 4 205-215℃, Zone 5 200-210℃, and Die head 195-205℃. The screw speed is controlled at 300-400 r / min, and the feeding speed is matched with the screw speed to ensure that the material residence time in the barrel is 1-2 min. After water cooling and air drying, the extruded melt is cut into uniform granules by a pelletizer and vacuum dried to obtain polypropylene composite masterbatch. Step 4: Add the dried composite masterbatch into a single screw extruder at an extrusion temperature of 190-210℃. After the melt is extruded through a T-die, it is cast onto a cooling roller with a surface temperature of 25-30℃ and rapidly cooled into a cast sheet. Step 5: Biaxial stretching is performed using a two-step method: first longitudinal stretching, then transverse stretching. The cast film is preheated to 110-130℃ for 30-60 seconds, and then longitudinally stretched at 115-135℃ with a stretching ratio of 3.5-4.5 times. After stretching, it is immediately cooled to room temperature. The longitudinally stretched film is then fed into a transverse stretching machine, preheated at 125-135℃ for 30-60 seconds, and then transversely stretched at 130-140℃ with a stretching ratio of 4.5-5.5 times. Step 6: The stretched film is heat-set at 125-135℃ for 15-25s, naturally cooled to room temperature, trimmed at the edges and then rolled up to obtain a polypropylene composite current collector base film with a thickness of 8-12μm.

[0022] The beneficial effects of this invention are as follows: 1. This invention constructs a uniformly dispersed, strongly interfacially bonded multiphase composite structure within a polypropylene matrix by compounding modified nano-montmorillonite with a multifunctional POSS-modified cyclotriphosphazene flame retardant enhancer, along with a maleic anhydride-grafted polypropylene compatibilizer and an optimized additive system. The base film prepared by this invention simultaneously possesses excellent mechanical properties, flame retardant properties, heat resistance, dimensional stability, and electrolyte resistance, meeting the stringent requirements for high-safety, high-energy-density lithium-ion battery current collectors.

[0023] 2. The POSS-modified cyclotriphosphazene flame retardant reinforcing agent synthesized in this invention uses a rigid six-membered cyclotriphosphazene ring as the core and grafts multiple cage-like silsesquioxane (POSS) structures through a mercapto-olefin click chemistry reaction, forming a phosphorus-nitrogen-silicon synergistic flame retardant system. In the flame retardant reinforcing agent, the heptaisobutyl organic side chain of POSS has good compatibility with the polypropylene molecular chain; the cage-like rigid structure of POSS synergistically works with the six-membered rigid ring of cyclotriphosphazene to effectively restrict the movement of the polypropylene molecular chain and improve the performance of the matrix; both the POSS cage-like structure and the cyclotriphosphazene core itself have high thermal stability; the hydrophobic cage-like structure of POSS can reduce the water absorption rate and electrolyte absorption rate of the base film. Therefore, the flame retardant reinforcing agent not only has excellent flame retardant properties but also enhances the interfacial compatibility, mechanical properties, thermal stability, and electrolyte resistance of the matrix.

[0024] 3. Modified nano-montmorillonite is obtained by first modifying sodium-based montmorillonite in situ with dopamine, and then performing thermal cross-linking treatment. Its two-dimensional layered structure can form a physical barrier network, hindering the thermal motion and heat conduction of polypropylene molecular chains. At the same time, the POSS-modified cyclotriphosphazene flame retardant reinforcing agent itself has excellent thermo-oxidative stability, which can increase the initial thermal decomposition temperature of the matrix. The synergistic effect of these three factors constructs a continuous and stable three-dimensional heat-resistant skeleton within the matrix, significantly reducing the coefficient of thermal expansion and high-temperature thermal shrinkage rate of the base film. This allows the base film to maintain good flatness and mechanical integrity even under the localized high temperatures generated during battery charging and discharging, thus avoiding the risk of short circuits between the positive and negative electrodes caused by thermal shrinkage of the base film. Detailed Implementation

[0025] The technical solution of the present invention is illustrated below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not preclude the existence of other method steps before or after the combined steps, or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention. Furthermore, unless otherwise stated, the numbering of each method step is merely a convenient tool for identifying each method step, and not for limiting the order of the method steps or defining the scope of the present invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the present invention.

[0026] To better understand the above technical solutions, exemplary embodiments of the present invention are described in more detail below. While exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the invention to those skilled in the art.

[0027] The present invention will be further described below with reference to the following embodiments.

[0028] Example 1

[0029] A polypropylene composite current collector base membrane, comprising, by weight parts: 100 parts of homopolymer polypropylene (melt flow index 3.0 g / 10 min, 230℃ / 2.16 kg), 6 parts of modified nano-montmorillonite, 12 parts of flame retardant reinforcing agent, 8 parts of maleic anhydride grafted polypropylene (PP-g-MAH, grafting rate 1.5 wt%, melt flow index 9 g / 10 min, 230℃ / 2.16 kg), 0.2 parts of antioxidant 1010, 0.4 parts of antioxidant 168, 0.35 parts of ultraviolet absorber UV-327, 0.25 parts of zinc stearate, and 0.25 parts of polyethylene wax.

[0030] The preparation methods of modified nano-montmorillonite include: 10g of sodium montmorillonite was dispersed in Tris-HCl buffer solution at pH 8.5 to prepare a 5% (w / w) suspension, and ultrasonically dispersed for 30 min. 2.5g of dopamine hydrochloride was added, and the mixture was stirred at room temperature in the dark for 24 h. After the reaction was completed, the mixture was centrifuged at 8000 r / min for 10 min, washed repeatedly with deionized water until the pH of the filtrate was neutral, vacuum dried at 60℃ for 10 h, placed in a tube furnace, heated to 150℃ at 5℃ / min under nitrogen protection, held for 2 h, naturally cooled, and passed through a 300-mesh sieve to obtain modified nano-montmorillonite.

[0031] The preparation methods of flame retardant reinforcing agents include: S1. Dissolve 3.48 g of hexachlorocyclotriphosphazene in 50 mL of anhydrous tetrahydrofuran to prepare a hexachlorocyclotriphosphazene solution; dissolve 6.53 g of allylamine (in excess, also acting as an acid-binding agent) in 30 mL of anhydrous tetrahydrofuran to prepare an allylamine solution. Under nitrogen protection and an ice bath, slowly add the allylamine solution dropwise to the hexachlorocyclotriphosphazene solution, controlling the addition time to 1 h. After the addition is complete, raise the temperature to 45 °C and react for 14 h. After the reaction is complete, cool to room temperature, filter to remove the generated allylamine hydrochloride precipitate, concentrate the filtrate to dryness at 40 °C using a rotary evaporator, and obtain a pale yellow viscous liquid. Wash the liquid three times with 20 mL of n-hexane each time, and then dry it under vacuum at 40 °C for 12 h to obtain the hexaallyltriphosphazene intermediate. S2. Under nitrogen protection, 12.0 g of mercaptopropyl-heptaisobutylsilsesquioxane (POSS-SH, molecular weight 893.6 g / mol) and 1.0 g of the above-mentioned hexaallyltriphosphazene intermediate were dissolved in 80 mL of N,N-dimethylformamide. 0.12 g of dimethyl benzoate (DMPA) was added as a photoinitiator, and the solution was tested under a UV lamp (365 nm, power density 10 mW / cm²).2 The reaction solution was irradiated and reacted at room temperature for 3 hours. After the reaction was completed, the reaction solution was poured into 500 mL of anhydrous ethanol to precipitate. The precipitate was collected by filtration, washed three times with 30 mL of anhydrous ethanol each time, and dried under vacuum at 60 °C for 12 hours to obtain POSS modified hexallyltriphosphazene flame retardant enhancer.

[0032] The preparation method of the above-mentioned polypropylene composite current collector film includes the following steps: Step 1: Vacuum dry all raw materials at 80℃ for 6 hours to remove moisture; Step 2: Add all the dried raw materials into a high-speed mixer and mix at 1200 r / min for 6 min to ensure that the components are evenly dispersed and to obtain a premix. Step 3: Add the premixed material to a twin-screw extruder for melt blending. The temperatures of each section of the twin-screw extruder are set as follows: Zone 1 185℃, Zone 2 195℃, Zone 3 205℃, Zone 4 210℃, Zone 5 205℃, and Die head 200℃. The screw speed is controlled at 350 r / min, and the feeding speed is matched with the screw speed to ensure that the material residence time in the barrel is 1.5 min. After water cooling and air drying, the extruded melt is cut into uniform particles by a pelletizer and vacuum dried at 80℃ for 6 h to obtain polypropylene composite masterbatch. Step 4: Add the dried composite masterbatch into a single screw extruder at an extrusion temperature of 200°C. After the melt is extruded through a T-die, it is cast onto a cooling roller with a surface temperature of 28°C and rapidly cooled into a cast sheet. Step 5: Bidirectional stretching is performed using a two-step method of first longitudinal stretching and then transverse stretching: the cast film is preheated to 120°C for 45 seconds, and then longitudinally stretched at 125°C with a stretching ratio of 4 times. After stretching, it is immediately cooled to room temperature. The longitudinally stretched film is then fed into a transverse stretching machine, preheated at 130°C for 45 seconds, and then transversely stretched at 135°C with a stretching ratio of 5 times. Step 6: The stretched film is heat-set at 130℃ for 20s, naturally cooled to room temperature, trimmed at the edges and then rolled up to obtain a polypropylene composite current collector base film with a thickness of 10μm.

[0033] Example 2

[0034] A polypropylene composite current collector base membrane, comprising, by weight parts: 100 parts of homopolymer polypropylene (melt flow index 2.0 g / 10 min, 230℃ / 2.16 kg), 3 parts of modified nano-montmorillonite, 10 parts of flame retardant reinforcing agent, 6 parts of maleic anhydride grafted polypropylene (PP-g-MAH, grafting rate 1.0 wt%, melt flow index 6 g / 10 min, 230℃ / 2.16 kg), 0.2 parts of antioxidant 1010, 0.2 parts of antioxidant 168, 0.2 parts of ultraviolet absorber UV-770, 0.1 parts of zinc stearate, and 0.2 parts of polyethylene wax.

[0035] The preparation methods of modified nano-montmorillonite include: 10g of sodium montmorillonite was dispersed in Tris-HCl buffer solution at pH 8.5 to prepare a 5% (w / w) suspension, and ultrasonically dispersed for 30 min. 2.5g of dopamine hydrochloride was added, and the mixture was stirred at room temperature in the dark for 24 h. After the reaction was completed, the mixture was centrifuged at 8000 r / min for 10 min, washed repeatedly with deionized water until the pH of the filtrate was neutral, vacuum dried at 60℃ for 10 h, placed in a tube furnace, heated to 150℃ at 5℃ / min under nitrogen protection, held for 2 h, naturally cooled, and passed through a 300-mesh sieve to obtain modified nano-montmorillonite.

[0036] The preparation methods of flame retardant reinforcing agents include: S1. Dissolve 3.48 g of hexachlorocyclotriphosphazene in 50 mL of anhydrous tetrahydrofuran to prepare a hexachlorocyclotriphosphazene solution; dissolve 5.71 g of allylamine in 30 mL of anhydrous tetrahydrofuran to prepare an allylamine solution. Under nitrogen protection and an ice bath, the allylamine solution was slowly added dropwise to the hexachlorocyclotriphosphazene solution over 1 hour. After the addition was complete, the temperature was raised to 40 °C and the reaction was carried out for 16 hours. After the reaction was completed, the mixture was cooled to room temperature, and the allylamine hydrochloride precipitate was removed by filtration. The filtrate was concentrated to dryness at 40 °C using a rotary evaporator to obtain a pale yellow viscous liquid. The liquid was washed three times with 20 mL of n-hexane each time, and then dried under vacuum at 40 °C for 12 hours to obtain the hexaallyltriphosphazene intermediate. S2. Under nitrogen protection, 11.5 g of mercaptopropyl-heptaisobutylsilsesquioxane (POSS-SH, molecular weight 893.6 g / mol) and 1.0 g of the above-mentioned hexaallyltriphosphazene intermediate were dissolved in 80 mL of N,N-dimethylformamide. 0.0575 g of dimethyl benzoate (DMPA) was added as a photoinitiator, and the solution was tested under a UV lamp (365 nm, power density 10 mW / cm²). 2 The reaction solution was irradiated and reacted at room temperature for 4 hours. After the reaction was completed, the reaction solution was poured into 500 mL of anhydrous ethanol to precipitate. The precipitate was collected by filtration, washed three times with 30 mL of anhydrous ethanol each time, and dried under vacuum at 60 °C for 12 hours to obtain POSS modified hexallyltriphosphazene flame retardant enhancer.

[0037] The preparation method of the above-mentioned polypropylene composite current collector film includes the following steps: Step 1: Vacuum dry all raw materials at 80℃ for 6 hours to remove moisture; Step 2: Add all the dried raw materials into a high-speed mixer and mix at 1000 r / min for 8 min to ensure that the components are evenly dispersed and to obtain a premix. Step 3: Add the premixed material to a twin-screw extruder for melt blending. The temperature settings for each section of the twin-screw extruder are: Zone 1 180℃, Zone 2 190℃, Zone 3 200℃, Zone 4 205℃, Zone 5 200℃, and Die head 195℃. The screw speed is controlled at 300 r / min, and the feeding speed is matched with the screw speed to ensure that the material residence time in the barrel is 2 min. After water cooling and air drying, the extruded melt is cut into uniform particles by a pelletizer and vacuum dried at 80℃ for 6 h to obtain polypropylene composite masterbatch. Step 4: Add the dried composite masterbatch into a single screw extruder at an extrusion temperature of 190°C. After the melt is extruded through a T-die, it is cast onto a cooling roller with a surface temperature of 25°C and rapidly cooled into a cast sheet. Step 5: Biaxial stretching is performed using a two-step method: first longitudinal stretching, then transverse stretching. The cast film is preheated to 110°C for 60 seconds, and then longitudinally stretched at 115°C with a stretching ratio of 3.5 times. After stretching, it is immediately cooled to room temperature. The longitudinally stretched film is then fed into a transverse stretching machine, preheated at 125°C for 60 seconds, and then transversely stretched at 130°C with a stretching ratio of 4.5 times. Step 6: The stretched film is heat-set at 125°C for 25 seconds, naturally cooled to room temperature, trimmed at the edges, and then rolled up to obtain a polypropylene composite current collector base film with a thickness of 12 μm.

[0038] Example 3

[0039] A polypropylene composite current collector base membrane, comprising, by weight parts: 100 parts of homopolymer polypropylene (melt flow index 4.0 g / 10 min, 230℃ / 2.16 kg), 8 parts of modified nano-montmorillonite, 15 parts of flame retardant reinforcing agent, 10 parts of maleic anhydride grafted polypropylene (PP-g-MAH, grafting rate 2.0 wt%, melt flow index 12 g / 10 min, 230℃ / 2.16 kg), 0.25 parts of antioxidant 1010, 0.75 parts of antioxidant 168, 0.5 parts of ultraviolet absorber UV-312, 0.35 parts of zinc stearate, and 0.35 parts of polyethylene wax.

[0040] The preparation methods of modified nano-montmorillonite include: 10g of sodium montmorillonite was dispersed in Tris-HCl buffer solution at pH 8.5 to prepare a 5% (w / w) suspension, and ultrasonically dispersed for 30 min. 3.0g of dopamine hydrochloride was added, and the mixture was stirred at room temperature in the dark for 24 h. After the reaction was completed, the mixture was centrifuged at 8000 r / min for 10 min, washed repeatedly with deionized water until the pH of the filtrate was neutral, vacuum dried at 65℃ for 8 h, placed in a tube furnace, heated to 150℃ at 5℃ / min under nitrogen protection, held for 2 h, naturally cooled, and passed through a 300-mesh sieve to obtain modified nano-montmorillonite.

[0041] The preparation methods of flame retardant reinforcing agents include: S1. Dissolve 3.48 g of hexachlorocyclotriphosphazene in 50 mL of anhydrous tetrahydrofuran to prepare a hexachlorocyclotriphosphazene solution; dissolve 7.13 g of allylamine in 30 mL of anhydrous tetrahydrofuran to prepare an allylamine solution. Under nitrogen protection and an ice bath, the allylamine solution was slowly added dropwise to the hexachlorocyclotriphosphazene solution over a period of 1 hour. After the addition was complete, the temperature was raised to 50 °C and the reaction was carried out for 12 hours. After the reaction was completed, the mixture was cooled to room temperature, and the allylamine hydrochloride precipitate was removed by filtration. The filtrate was concentrated to dryness at 40 °C using a rotary evaporator to obtain a pale yellow viscous liquid. The liquid was washed three times with 20 mL of n-hexane each time, and then dried under vacuum at 40 °C for 12 hours to obtain the hexaallyltriphosphazene intermediate.

[0042] S2. Under nitrogen protection, 12.5 g of mercaptopropyl-heptaisobutylsilsesquioxane (POSS-SH, molecular weight 893.6 g / mol) and 1.0 g of the above-mentioned hexaallyltriphosphazene intermediate were dissolved in 80 mL of N,N-dimethylformamide. 0.1875 g of dimethyl benzoate (DMPA) was added as a photoinitiator, and the solution was tested under a UV lamp (365 nm, power density 10 mW / cm²). 2 The reaction solution was irradiated and reacted at room temperature for 5 hours. After the reaction was completed, the reaction solution was poured into 500 mL of anhydrous ethanol to precipitate. The precipitate was collected by filtration, washed three times with 30 mL of anhydrous ethanol each time, and dried under vacuum at 60 °C for 12 hours to obtain POSS modified hexallyltriphosphazene flame retardant enhancer.

[0043] The preparation method of the above-mentioned polypropylene composite current collector film includes the following steps: Step 1: Vacuum dry all raw materials at 80℃ for 6 hours to remove moisture.

[0044] Step 2: Add all the dried raw materials into a high-speed mixer and mix at 1500 r / min for 5 min to ensure that the components are evenly dispersed and to obtain a premix. Step 3: Add the premixed material to a twin-screw extruder for melt blending. The temperature settings for each section of the twin-screw extruder are: Zone 1 190℃, Zone 2 200℃, Zone 3 210℃, Zone 4 215℃, Zone 5 210℃, and Die head 205℃. The screw speed is controlled at 400 r / min, and the feeding speed is matched with the screw speed to ensure that the material residence time in the barrel is 1 min. After water cooling and air drying, the extruded melt is cut into uniform particles by a pelletizer and vacuum dried at 80℃ for 6 h to obtain polypropylene composite masterbatch. Step 4: Add the dried composite masterbatch into a single screw extruder at an extrusion temperature of 210°C. After the melt is extruded through a T-die, it is cast onto a cooling roller with a surface temperature of 30°C for rapid cooling into a cast sheet. Step 5: Biaxial stretching is performed using a two-step method: first longitudinal stretching, then transverse stretching. The cast film is preheated to 130°C for 30 seconds, and then longitudinally stretched at 135°C with a stretching ratio of 4.5 times. After stretching, it is immediately cooled to room temperature. The longitudinally stretched film is then fed into a transverse stretching machine, preheated at 135°C for 30 seconds, and then transversely stretched at 140°C with a stretching ratio of 5.5 times. Step 6: The stretched film is heat-set at 135°C for 15 seconds, naturally cooled to room temperature, trimmed at the edges, and then rolled up to obtain a polypropylene composite current collector base film with a thickness of 8 μm.

[0045] Comparative Example 1 (no flame retardant enhancer added compared to Example 1) Except for the absence of flame retardant reinforcing agent, the other raw material formulations and preparation methods are exactly the same as in Example 1, resulting in a polypropylene base film with a thickness of 10 μm.

[0046] Comparative Example 2 (compared to Example 1, the flame retardant enhancer was replaced with commercially available common flame retardant ammonium polyphosphate (APP)). The POSS-modified hexaallyltriphosphazene flame retardant reinforcing agent in Example 1 was replaced with an equal mass of commercially available ammonium polyphosphate (APP, degree of polymerization n > 1000). The other raw material formulations and preparation methods were exactly the same as in Example 1, resulting in a polypropylene composite base film with a thickness of 10 μm.

[0047] Comparative Example 3 (compared to Example 1, with the addition of unmodified hexaallyltriphosphazene) The POSS-modified hexaallyltriphosphazene flame retardant reinforcing agent in Example 1 was replaced with an equal mass of the hexaallyltriphosphazene intermediate prepared in step S1 of Example 1. The other raw material formulations and preparation methods were exactly the same as in Example 1, resulting in a polypropylene composite base film with a thickness of 10 μm.

[0048] Experimental testing The performance of the composite current collector base film prepared in Example 1 and Comparative Examples 1-3 was tested.

[0049] Detection methods (1) Mechanical properties: The longitudinal (MD) tensile strength and elongation at break of the film were tested using a universal testing machine in accordance with GB / T1040.3-2006 standard, with a tensile speed of 50 mm / min.

[0050] (2) Flame retardant performance: The limiting oxygen index (LOI) was tested according to GB / T2406.2-2009 standard.

[0051] (3) Heat resistance dimensional stability: Cut the film into 100mm×100mm square samples, place them in an oven at 150℃ for 30min, take them out and cool them to room temperature, measure the dimensional change, and calculate the heat shrinkage rate.

[0052] (4) Electrolyte resistance: The film was cut into standard tensile specimens and immersed in 1 mol / L LiPF6 (EC:DMC:EMC volume ratio 1:1:1) electrolyte and sealed and stored at 60℃ for 7 days. After removal, it was rinsed with anhydrous ethanol, dried at room temperature for 24 h, and the tensile strength was tested and the retention rate was calculated; at the same time, the mass change before and after immersion was tested and the mass change rate was calculated.

[0053] The test results are as follows:

[0054] The test results show that the longitudinal tensile strength of Example 1 reached 118 MPa, which is higher than that of Comparative Examples 1-3. This indicates that the POSS-modified hexallyltriphosphazene flame retardant reinforcing agent of the present invention not only has a flame retardant effect but also synergistically enhances the film with the modified nano-montmorillonite, significantly improving the mechanical properties of the film. The limiting oxygen index of Example 1 reached 33.2%, which is better than that of Comparative Examples 1-3. This indicates that the POSS-modified hexallyltriphosphazene flame retardant reinforcing agent of the present invention has excellent flame retardant effect. The longitudinal thermal shrinkage rate of Example 1 after being placed at 150°C for 30 min was only 0.82%, which is much lower than that of Comparative Examples 1-3. This may be because the introduction of the POSS group increases the glass transition temperature and heat resistance of the film, and the layered structure of the modified nano-montmorillonite can also effectively restrict the thermal motion of the molecular chains. After being immersed in electrolyte at 60°C for 7 days, the tensile strength retention rate of Example 1 was still 94.3%, and the mass change rate was 0.32%, which was better than that of Comparative Examples 1-3. This shows that the composite base film of the present invention has excellent resistance to electrolyte corrosion and can meet the requirements for long-term use of lithium-ion batteries.

[0055] In summary, the polypropylene composite current collector base film prepared by the present invention using POSS-modified hexamethylenetriphosphazene flame retardant enhancer and modified nano-montmorillonite in synergy simultaneously possesses excellent mechanical properties, flame retardant properties, heat resistance, dimensional stability, and electrolyte resistance, and can meet the stringent requirements for high-safety, high-energy-density lithium-ion battery current collectors.

[0056] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms should not be construed as necessarily referring to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. In addition, those skilled in the art can combine and integrate the different embodiments or examples described in this specification.

[0057] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A polypropylene composite current collector-based membrane, characterized in that, Calculated by weight, including: 100 parts polypropylene resin, 3-8 parts modified nano-montmorillonite, 10-15 parts flame retardant reinforcing agent, 6-10 parts compatibilizer, 0.4-1.0 parts antioxidant, 0.2-0.5 parts ultraviolet absorber and 0.3-0.7 parts lubricant; The modified nano-montmorillonite is obtained by first modifying sodium-based montmorillonite in situ with dopamine, and then subjecting it to heat treatment.

2. The polypropylene composite current collector-based membrane according to claim 1, characterized in that, The polypropylene resin is homopolymer polypropylene, with a melt flow index of 2.0-4.0 g / 10 min at 230°C and 2.16 kg; the compatibilizer is maleic anhydride-grafted polypropylene, with a grafting rate of 1.0-2.0 wt%, and a melt flow index of 6-12 g / 10 min at 230°C and 2.16 kg.

3. The polypropylene composite current collector-based membrane according to claim 1, characterized in that, The preparation method of the modified nano-montmorillonite includes: 10g of sodium montmorillonite was dispersed in Tris-HCl buffer to prepare a 5% (w / w) suspension, and ultrasonically dispersed. 2-3g of dopamine hydrochloride was added, and the mixture was stirred and reacted at room temperature in the dark for 12-36 hours. After the reaction was completed, the mixture was centrifuged, washed, vacuum dried, and heat-treated in a tube furnace at 150℃. After natural cooling, the mixture was sieved to obtain modified nano-montmorillonite.

4. The polypropylene composite current collector-based membrane according to claim 1, characterized in that, The antioxidant is a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1-3.

5. The polypropylene composite current collector-based membrane according to claim 1, characterized in that, The ultraviolet absorber is at least one of UV-327, UV-770, and UV-312.

6. The polypropylene composite current collector-based membrane according to claim 1, characterized in that, The lubricant is a compound of zinc stearate and polyethylene wax in a mass ratio of 1-2:1-2.

7. The polypropylene composite current collector-based membrane according to claim 1, characterized in that, The preparation method of the flame retardant enhancer includes: S1. Prepare solutions of hexachlorocyclotriphosphazene and allylamine separately. Under nitrogen protection and ice bath conditions, slowly add the allylamine solution to the hexachlorocyclotriphosphazene solution. After the addition is complete, heat to 40-50℃ and react for 12-16 hours. After the reaction is complete, cool to room temperature, filter to remove the precipitate, rotate to dryness, and then wash and dry to obtain the hexaallyltriphosphazene intermediate. S2. Under nitrogen protection, mercaptopropyl-heptaisobutylsilsesquioxane and hexaallyltriphosphazene intermediates are dissolved in N,N-dimethylformamide, a photoinitiator is added, and the reaction solution is irradiated with ultraviolet light. The reaction is carried out at room temperature for 3-5 hours. After the reaction is completed, the flame retardant enhancer is obtained by precipitation, filtration, washing and drying.

8. The polypropylene composite current collector-based membrane according to claim 7, characterized in that, In S1, the mass ratio of hexachlorocyclotriphosphazene to allylamine is 3.48:5.71-7.

13.

9. The polypropylene composite current collector-based membrane according to claim 1, characterized in that, In S2, the mass ratio of mercaptopropyl-heptaisobutylsilsesquioxane to hexaallyltriphosphazene intermediate is 11.5-12.5:1; the photoinitiator is benzoin dimethyl ether, and the amount added is 0.5%-1.5% of the mass of mercaptopropyl-heptaisobutylsilsesquioxane.

10. A method for preparing the polypropylene composite current collector-based membrane according to claim 1, characterized in that, Includes the following steps: Step 1: Dry all raw materials before use; Step 2: Accurately weigh each dried raw material according to the weight proportions, add all raw materials into a high-speed mixer to disperse each component evenly and obtain a premix; Step 3: Add the premix to a twin-screw extruder for melt blending. After water cooling and air drying, the extruded melt is cut into uniform particles by a pelletizer and vacuum dried to obtain polypropylene composite masterbatch. Step 4: Add the dried composite masterbatch into a single-screw extruder. After the melt is extruded through a T-die, it is rapidly cooled into a cast sheet. Step 5: The casting sheet is stretched bidirectionally using a two-step method of first longitudinal stretching and then transverse stretching. Step 6: Heat-set the stretched film, allow it to cool naturally to room temperature, trim the edges, and then roll it up to obtain a polypropylene composite current collector base film.